Impact of aortic stiffness on the frequency of paroxysmal atrial fibrillation recurrences - Kızılırmak, Filiz; Babür Güler, Gamze; Güler, Ekrem; Güneş, Hacı Murat; Demir, Gültekin Günhan; Omaygenç, Mehmet Onur; Çakal, Beytullah; Olgun, Fatih Erkam; Köklü, Erkan; Kılıçaslan, Fethi (Taylor & Francis, 2015)
Background The relationship between arterial stiff ness (AS) and atrial fi brillation (AF) incidence is well-known. In this study we aimed to investigate the relationship between AS parameters and AF occurence as well as AF recurrence post catheter ablation (CA) in patients with paroxysmal AF (PAF). Methods We enrolled 103 patients with PAF diagnosis and 103 control subjects with similar demographic characteristics. We measured AS parameters and central aortic pressure (CAP) parameters by an oscillometric device in both groups. In the patient group 51 patients underwent CA for AF and recurrence rates at 3 and 6 months postprocedurally were recorded. AS parameters were compared between patients with and without AF recurrence. Results In the PAF patient group central systolic pressure, central diastolic pressure, central pulse pressure, augmentation pressure, augmentation index, and pulse wave velocity were signifi cantly higher than in the control group (for each listed parameter P < 0.05). AS parameters were not associated with AF recurrence post CA. Left atrial size (LAS) was found as an independent predictor for recurrence in multivariate analysis (?: 2.30; P = 0.02; OR: 9.97; 95% CI [1.28-77.48]). Conclusion Increased AS is associated with PAF occurence. Nevertheless, LAS, a traditional risk factor, was the most powerful predictor for recurrence post CA; whereas AS or CAP were not associated with recurrence.
Keywords: Arterial Stiff Ness; Atrial Fi Brillation; Catheter Ablation